ALIH AKSARA DAN ALIH BAHASA TEKS KISAH NABI ADAM ‘ALAIHISSALAM DALAM NASKAH QISHASHUL ANBIYA’ VERSI AZHARI AL-KHALIDI RAHMATULLAH - Anti, Afni; Hasanuddin WS, Hasanuddin WS; Nurizzati, Nurizzati (Universitas Negeri Padang, 2014)
This article was written to: (1) describe of text story about Adam prophet at text Story of Prophets version Azhari Al-Khalidi Rahmatullah; (2) describe the translation of story about Adam prophet at text Story of Prophets version Azhari Al-Khalidi Rahmatullah; (3) describe change language of story about Adam prophet at text Story of Prophets version Azhari Al-Khalidi Rahmatullah. The objeck of this study were story about Adam prophet at text Story of Prophets version Azhari Al-Khalidi Rahmatullah. The text was data processing by four step, is roundup of data, describe of the text, translation, and change language. The finding of the study is avalaible of text about Adam prophet at text Story of Prophets version Azhari Al-Khalidi Rahmatullah in Latin script and Indonesian language and more words that indicate old language charactheristic.